2015
DOI: 10.1080/01459740.2015.1102248
|View full text |Cite
|
Sign up to set email alerts
|

Class, Social Suffering, and Health Consumerism

Abstract: In recent years an extensive social gradient in cancer outcome has attracted much attention, with late diagnosis proposed as one important reason for this. Whereas earlier research has investigated health care seeking among cancer patients, these social differences may be better understood by looking at health care seeking practices among people who are not diagnosed with cancer. Drawing on long-term ethnographic fieldwork among two different social classes in Denmark, our aim in this article is to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…A key finding was that the association between education and likelihood of making a cancer attribution was independent of cancer avoidance . Potential explanations for lower likelihood of mentioning cancer in response to the vignettes in the lower educated groups include lower cancer awareness , higher fatalism , and wider social and cultural barriers .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A key finding was that the association between education and likelihood of making a cancer attribution was independent of cancer avoidance . Potential explanations for lower likelihood of mentioning cancer in response to the vignettes in the lower educated groups include lower cancer awareness , higher fatalism , and wider social and cultural barriers .…”
Section: Discussionmentioning
confidence: 93%
“…Previous research suggested that people from lower SES backgrounds may have lower knowledge of cancer warning signs , or are less likely to consider cancer as a possible cause when they experience ‘alarm’ symptoms in everyday life . Studies indicate that processes involved could include higher levels of cancer avoidance , higher levels of cancer fatalism , or wider physical, political and social issues in people from lower socioeconomic backgrounds . Recent evidence from cancer patients reported socio‐demographic differences in symptom attributions, with patients from lower educational levels more likely to attribute their most important symptom to psychological causes .…”
Section: Introductionmentioning
confidence: 99%
“…29 It has been argued that the current structure of the clinical encounter in general practice, which is characterised by strict time limitations and focus on only one medical complaint at a time, does not encourage all patient groups to seek general practice for health problems. 30,31 Some patients may thus be discouraged from seeking care on a regular basis, which questions the accessibility of general practice. European patients generally assess the accessibility of general practice/GPs as low.…”
Section: Implications For Practicementioning
confidence: 99%
“…In this study, the high‐SEP population displayed a more proactive health consumer lifestyle focusing on body maintenance than people with low SEP. The latter were occupied with social and physical problems and demands, and challenges with the social services (Merrild, Risor, Vedsted, & Andersen, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the high-SEP population displayed a more proactive health consumer lifestyle focusing on body maintenance than people with low SEP. The latter were occupied with social and physical problems and demands, and challenges with the social services(Merrild, Risor, Vedsted, & Andersen, 2016).Smoking and unhealthy diets were unevenly distributed among patients with high and low SEP and were associated with CR attendance. This finding might be explained by a model of health-relevant cultural capital including health values, perceptions, health knowledge and behavioural norms that form the bases of lifestyle patterns(Abel, 2008).…”
mentioning
confidence: 99%